Urgensi Perlindungan Sosial Cuti Haid terhadap Tenaga Kerja Perempuan - lianto, Vina; Najicha, Fatma Ulfatun (Fakultas Hukum Universitas PGRI Kanjuruhan Malang, 2022)
Manpower is one of many fields in Indonesia which has the aim of advancing the Indonesian Economy and National Development. Female Labor is also one of the subjects of Indonesian’s economic development. The basic difference between male and female workers makes it nacessary to have several rights obtained, one of which is the right to menstrual leave which is obtained by female workers in Indonesian. The implementation that occurs in Indonesian companies reflects that many people care about the equalization of women’s rights. There are many obtacles and obtacles in implementing this menstrual leave right. But this does not make some companies , especially companies that have been counted large, ignore the Menstrual Leave Rights. Because indeed this right is one of the many rights that should be obtained by a women. This right is also protected by law and should be exercised.